PEMBUATAN VIDEO ANIMASI PENDEK 2 DIMENSI “MEMBUAT KARTU TANDA PENDUDUK BARU” - Widda Aulia, Kirana; Yusni Nyura; Subhan Hartanto (Jurnal Media Akademik (JMA), 2024)
This study aims to create a 2D animated video containing the requirements and flow for making a new ID card, which is used to educate people who do not yet have an ID card. This video contains information about the required documents and the stages of making them. In making this 2-dimensional animated video, the Multimedia Development Life Cycle (MDLC) design method is used, which includes several stages, namely Concept, Design, Material Collecting, Assembly, Testing, and Distribution. After going through these stages, the resulting video can be used as an educational medium for high school students who do not yet have an ID card. This study uses Celtx to create scripts and storyboards, and Canva to combine assets in the video and add sound effects and narration. This study produces a short 2-dimensional animated video with a duration of one minute and fourty seconds containing the requirements and flow for making a new ID card.